Analytical estimation of switched reluctance motor flux linkage profile by using evolutionary algorithm and numerical simulations - Barukčić, Marinko (JET on-line, 2017)
The objective of this paper is to research the possibility of approximating a switched reluctant motor (SRM) flux linkage with respect to rotor angle and current with an analytical expression. The flux linkage per phase of the reluctance motor stator winding is obtained numerically for different rotor positions. The numeric values of the stator flux linkage are calculated with Finite Element Method (FEM) software FEMM (Finite Element Method Magnetics). After the flux linkage values are obtained the function estimate is proposed. This function represents the change in the stator flux linkage with respect to rotor angle. The form of proposed function is based on the curve shape obtained from FEMM. The proposed analytical expression contains some parameters with unknown values that need to be determined. The Evolutionary Algorithm (EA) is used for this purpose. The problem of finding function parameters is defined in the form of the optimization problem, which is solved by EA. The problem objective function is defined as the difference between the flux linkage values obtained by using FEMM and calculated by using the proposed analytical expression. The above procedure is performed for a few specified current values. The flux linkage values for any current values are obtained by linearization between specified current values. The proposed analytical model of the motor flux linkage can be implemented in simulation model of the SRM with the aim of controlling it. Furthermore, the SRM inductance profile can be easily obtained by dividing the proposed flux model by current.
Keywords: estimation; evolucijski algoritem; evolutionary algorithm; flux linkage profile; magnetni sklepi; metoda končnih elementov; numerical simulation; numerična simulacija; switched reluctance motor